Pulmonary haemodynamics during recovery from maximum incremental cycling exercise. Issue 1 (28th April 2016) - Oliveira, Rudolf K.F.; Waxman, Aaron B.; Agarwal, Manyoo; Badr Eslam, Roza; Systrom, David M.
Assessment of cardiac function during exercise can be technically demanding, making the recovery period a potentially attractive diagnostic window. However, the validity of this approach for exercise pulmonary haemodynamics has not been validated. The present study, therefore, evaluated directly measured pulmonary haemodynamics during 2-min recovery after maximum invasive cardiopulmonary exercise testing in patients evaluated for unexplained exertional intolerance. Based on peak exercise criteria, patients with exercise pulmonary hypertension (ePH; n=36), exercise pulmonary venous hypertension (ePVH; n=28) and age-matched controls (n=31) were analysed. By 2-min recovery, 83% (n=30) of ePH patients had a mean pulmonary artery pressure (mPAP) <30 mmHg and 96% (n=27) of ePVH patients had a pulmonary arterial wedge pressure (PAWP) <20 mmHg. Sensitivity of pulmonary hypertension-related haemodynamic measurements during recovery for ePH and ePVH diagnosis was ≤25%. In ePVH, pulmonary vascular compliance (PVC) returned to its resting value by 1-min recovery, while in ePH, elevated pulmonary vascular resistance (PVR) and decreased PVC persisted throughout recovery. In conclusion, we observed that mPAP and PAWP decay quickly during recovery in ePH and ePVH, compromising the sensitivity of recovery haemodynamic measurements in diagnosing pulmonary hypertension. ePH and ePVH had different PVR and PVC recovery patterns, suggesting differences in the underlying pulmonary hypertension pathophysiology. Pulmonary vascular pressures quickly recover after exercise, but patterns differ between exercise PH and exercise PVH http://ow.ly/ZFGwk